Unsteady Flow of Rotating Brinkman Type Fluid in Moving Disk - Ahmad Qushairi, Mohamad; Muhamad Najib, Zakaria; Khan, Ilyas; Sharidan, Shafie; Zulkhibri, Ismail (Akademi Sains Malaysia, 2020)
In this paper, the exact solution for unsteady flow of rotating Brinkman type fluid over a moving disk is investigated. The momentum governing equation is modelled in the form of Partial Differential Equation together with the initial and boundary conditions. Using the suitable non-dimensional variables, the momentum governing equation as well as initial and boundary conditions are reduced to non-dimensional equations. The expressions of velocity and skin friction are obtained by using the Laplace transform method. Then, they are plotted graphically and discussed for different values of parameters such as Brinkman type fluid, rotation, and time. The obtained solution is satisfied for both initial and boundary conditions and skin friction shows the opposite behaviour to the velocity of the fluid.